Young Children's Creative Thinking - Fumoto Hiroko; Greenfield Sue; Hargreaves David; Robson Sue (Sage, 2012)
This book brings an interplay of theory, research and practice to provide a fresh yet penetrating perspective on young children's creative thinking in the context of their relationships with others. Acknowledgements, Introduction, Creative Thinking and Social Relationships and Early Childhood Practice, Creative Thinking in Early Childhood, Social Relationships in Early Childhood, Exploring Perspectives in Early Childhood Research, Children's Voices: Young Children as Participants in Research, Involving Parents in Research, Researchers and Practitioners Collaborating on Research, Experiences of Young Children and Parents and Practitioners, Children's Experiences of Creative Thinking, Parents' Experiences of Supporting Young Children's Creative Thinking, Practitioners' Experiences of Supporting Young Children's Creative Thinking, Conclusions: Towards Understanding Young Children's Creative Thinking, References, Index.